Oral health, the patient's perspective during the COVID 19 pandemic - Paun, Ariadna Georgiana Eugenia; Chifor, Radu; Radu, Constantin; Strilciuc, Ștefan; Badea, Iulia Clara; Borzan, Cristina Maria (Medicine and Pharmacy Reports, 2022)
Background and aims. On March 16, 2020, the state of emergency was established with drastic measures of isolation and quarantine. Among the measures taken in the context of the state of emergency was the closure of dental offices throughout the country. The aim of our questionnaire-based cross-sectional study was to identify the psycho-affective implications of the Romanian citizens induced by the COVID-19 pandemic period as well as their opinion related to the self-perceived oral health status during this period. Methods. An original questionnaire was designed consisting of 41 questions, which were distributed to the general population via the Internet. The first part of the questionnaire investigated the respondents’ opinion regarding the impact of this COVID-19 pandemic period of isolation on their oral health and the attention paid by the subjects to oral hygiene during restrictions. The second part refers to their addressability to the dental services during this pandemic and the third part interrogates different characteristics, namely the presence of comorbidities, possible anxiety, and stress. Results. A total of 769 participants answered the questionnaire online. Conclusion. According to their responses most of the respondents were not afraid of the possibility of contracting Sars-Cov-2 during dental treatments, but were in certain periods deprived of accessing dental services due to lockdown restrictions. They are aware of their oral health problems and pay more attention to oral hygiene so that they do not get worse during restrictions.